The Epigenetic Mechanisms Underlying Thermomorphogenesis and Heat Stress Responses in Arabidopsis - Anna Zioutopoulou (MDPI AG, 2021)
Integration of temperature cues is crucial for plant survival and adaptation. Global warming is a prevalent issue, especially in modern agriculture, since the global rise in average temperature is expected to impact crop productivity worldwide. Hence, better understanding of the mechanisms by which plants respond to warmer temperatures is very important. This review focuses on the epigenetic mechanisms implicated in plant responses to high temperature and distinguishes the different epigenetic events that occur at warmer average temperatures, leading to thermomorphogenic responses, or subjected to extreme warm temperatures, leading to heat stress.